Definition of retail electricity prices for industrial consumers - Дорошенко, Олександр Іванович; Пєсков, Сергій Анатолійович; Сєргатий, Андрій Миколайович; Борисенко, Світлана Олександрівна (Technology audit and production reserves, 2015)
Based on the physics of normal electric power supply, in the article it is proposed a new, science-based approach to determine the retail price of electricity for industrial consumers and equivalent to them for which it is accounted an impact of reactive load of specific electricity consumer on the economics of the electricity transmission process. Given that pricing in the electricity system is the basic calculation system, which determines its functioning economy, it is proposed two levels of it: the base (wholesale) and retail. Principles for determining the retail electricity price are scientifically based in the article, which take into account the physics of the impact of voltage in the power grid on pricing for consumers, its active loss and bandwidth depending on the power reactive load of particular consumer of electricity, which is the basis of the methodology for determining the retail price of consumed electricity.